(untitled) (Педагогіка вищої та середньої школи, 2009)
The part and the functions of emotions as a necessity of harmonizing of interaction of emotional and intellectual factors during studying process as an important means of rising of effectiveness of a methodic work for quality education are being substantiated in the article.